The Rheumatobates Bergroth, 1892 (Hemiptera: Heteroptera: Gerridae) of Colombia, including the description of R. plumipes n. sp. and a key to represented species - Castro-Vargas, Maria I.; Morales-Castaño, Irina T. (Zootaxa, 2011)
Nine species of Rheumatobates are recorded from Colombia. Rheumatobates plumipes n. sp. is described. New departamental records are presented for R. imitator (Córdoba) and R. crassifemur crassifemur (Caquetá), and the geographical range of R. clanis is expanded to Colombia. The general habitus of males and females is illustrated. A key for the species of the genus found in Colombia is also provided.